Lead time optimization and review of planning criteria for a food packaging company - Sudhir, Priyanka (2014)
An opportunity for reduction in WIP and lead time of the Singapore operations of a multi-national food products packaging company was identified during a study of the system in accordance with the World Class Manufacturing philosophy. Changes in planning policy were proposed to remedy the problem and simulation models were used, on the make- to-order, serial production system to test three potential solutions to the problem. The models used showed great promise for reduction in WIP and the lead time for both the priority and ordinary products. The role of design as a sorting criterion on the printer was also investigated by a fundamental integer programming model using the Traveling Salesman approach. Results confirming the significance of design in the printer setup process were obtained in the trial run.